Born global’s Risk Perception and Internationalization in Emerging Markets - Stocker, Fabricio; Manuela Cunha de Mascena, Keysa; Abib, Gustavo; Arthur Reis Irigaray, Hélio (Review of Business Management, 2022)
Purpose - The purpose of this paper is to propose an integrative model of risk analysis and influencing factors on the propensity and speed of the born globals internationalization process. Theoretical framework - The research is based on the international business literature focusing on the risk on internationalization. The variables, and scale used to construct the model comes from the referred literature, supported by recent studies. Design/methodology/approach - The model is tested by a survey carried out on a sample of 200 Brazilian microbreweries and the data are analyzed using structural equation modeling. Findings - The findings indicate that the speed of internationalization, which involves the process, strategy, and networks, has a strong relationship with the risk perception. In contrast, the internationalization propensity, which involves the characteristics of the entrepreneur is not related to the risk evaluation. Originality - This study seeks to improve the knowledge proposing a structural model and empirically testing the constructs of the propensity for and speed of internationalization and the impact of the evaluation and perception of risks on born globals. Research implications - This study further complements and enriches the research of risk perception in the field of international entrepreneurship, and contributes to the literature in emerging markets, discussing the characteristics of entrepreneurship and small businesses within this context. Practical implications - The relationship networks influence the process and speed of internationalization of BGs, as well as the perception and assessment of risk by entrepreneurs, highlighting the importance of this discussion in practice. Keywords Risk perception, Internationalization, Born globals, Emerging Markets.